Evaluation of Seasonal Factors on Petroleum Hydrocarbon Vapor Biodegradation and Intrusion Potential in a Cold Climate. Issue 4 (23rd December 2014) - Hers, Ian; Jourabchi, Parisa; Lahvis, Matthew A.; Dahlen, Paul; Luo, E. Hong; Johnson, Paul; DeVaull, George E.; Mayer, K. Ulrich
Abstract A detailed seasonal study of soil vapor intrusion at a cold climate site with average yearly temperature of 1.9 °C was conducted at a house with a crawlspace that overlay a shallow dissolved‐phase petroleum hydrocarbon (gasoline) plume in North Battleford, Saskatchewan, Canada. This research was conducted primarily to assess if winter conditions, including snow/frost cover, and cold soil temperatures, influence aerobic biodegradation of petroleum vapors in soil and the potential for vapor intrusion. Continuous time‐series data for oxygen, pressure differentials, soil temperature, soil moisture, and weather conditions were collected from a high‐resolution monitoring network. Seasonal monitoring of groundwater, soil vapor, crawlspace air, and indoor air was also undertaken. Petroleum hydrocarbon vapor attenuation and biodegradation rates were not significantly reduced during low temperature winter months and there was no evidence for a significant capping effect of snow or frost cover that would limit oxygen ingress from the atmosphere. In the residual light nonaqueous phase liquid (LNAPL) source area adjacent to the house, evidence for biodegradation included rapid attenuation of hydrocarbon vapor concentrations over a vertical interval of approximately 0.9 m, and a corresponding decrease in oxygen to less than 1.5% v/v. In comparison, hydrocarbon vapor concentrations above the dissolved plume and below the house were much lower and decreased sharply within a few tens of centimeters above the groundwater source. Corresponding oxygen concentrations in soil gas were at least 10% v/v. A reactive transport model (MIN3P‐DUSTY) was initially calibrated to data from vertical profiles at the site to obtain biodegradation rates, and then used to simulate the observed soil vapor distribution. The calibrated model indicated that soil vapor transport was dominated by diffusion and aerobic biodegradation, and that crawlspace pressures and soil gas advection had little influence on soil vapor concentrations.